Prevention is Better Than Cure: State Intervened Risk Assessment Screening to Protect Potential Victims of Domestic Violence - Piranethaa, P. (Faculty of Arts, University of Jaffna & Surana and Surana International Attorneys, 2026)
Severe impacts of intimate partner violence have been deemed to be a public health crisis, but the legal framework remains merely reactive, which intervenes only after the harm has taken place. Existing literature lacks a proactive, preventive mechanism that identifies risk factors of intimate partner violence prior to the first instance of abuse, especially within the pre-marital context, where early intervention can be done to disrupt the abusive cycle of coercive control. This research paper proposes a novel, prevention-based legal framework that intends to integrate affective computing to screen for linguistic and vocal indicators of coercive control during mandatory pre-marital interviews. With scenario-based dialogues, the system extracts measurable behavioural and acoustic data such as speech patterns and lexicon choices associated with domination, isolation, and micro regulation to flag potential risk while refraining from diagnosing emotions or intent. It is argued that such a tool with robust safeguards, including communal oversight, transparency protocols and clauses, may fulfil the state’s positive duty to prevent foreseeable harm while also balancing individual autonomy and privacy. By changing Intimate Partner Intervention from reaction to prevention, this research offers a contemporary, ethics-based model that receives public health screening as a means of protecting relational integrity and reducing systemic violence.